UPAYA JOINT NATIONS PROGRAM ON HIV/AIDS (UNAIDS) DALAM PENANGANAN HIV/AIDS DI NIGERIA - Yulman Suhendra; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research explains the role of international organizations in dealing with HIV / AIDS that occurred in Nigeria in 2010. One of the countries with highest HIV / AIDS transmission rate is Nigeria. Joint Nations Program On HIV / AIDS (UNAIDS) has the task of handling HIV / AIDS in accordance with the mandate given by the United Nations.This research uses descriptive analytic research method. Data obtained by books, journals, articles, dictionaries and websites. The theory used in this research is the theory of international organizationsThis research demonstrates UNAIDS's efforts in dealing with HIV / AIDS in Nigeria and has made an active role in providing its aid in Nigeria in the form of facilities and funding to Nigeria. With the cooperation of UNAIDS and the Nigerian government have a direct positive impact on HIV / AIDS in Nigeria.Keywords:UNAIDS,Nigeria UNAIDS